2011
DOI: 10.17221/3838-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between housing system and genotype in relation to internal and external egg quality parameters

Abstract: ABSTRACT:The effect of three housing systems (conventional cages, enriched cages and litter) on egg quality parameters was evaluated in two experiments with four brown laying strains ISA Brown, Hisex Brown, Bovans Brown and Moravia BSL. During 40 weeks of lay the total number of 7200 eggs was produced and analysed for egg weight, egg component weight and eggshell quality indicators. In 60 eggs, pore density in the small-end, large-end and equatorial areas was determined. Significant interactions between genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 21 publications
(36 reference statements)
2
15
1
1
Order By: Relevance
“…Significantly higher shape index and deformation were determined in Czech hen compared to eggshell weight where higher values were found in Lohmann white. Similar results were confirmed also by Tůmová et al (2011). Main deviations in egg composition, egg weight and eggshell quality are between brown and white hybrids (Singh et al, 2009).…”
Section: Tablesupporting
confidence: 80%
“…Significantly higher shape index and deformation were determined in Czech hen compared to eggshell weight where higher values were found in Lohmann white. Similar results were confirmed also by Tůmová et al (2011). Main deviations in egg composition, egg weight and eggshell quality are between brown and white hybrids (Singh et al, 2009).…”
Section: Tablesupporting
confidence: 80%
“…Samiullah et al (3) found that egg weight, Haugh unit, shell weight, shell ratio, and shell thickness values of eggs in a conventional-cage system were higher than those of eggs in a free-range system and, similar to our results, those values increased with flock age, except for Haugh unit, which decreased. However, in other studies there were no differences between housing systems for shell weight (14,16) and Haugh unit (17). In this study generally the temperature was low in the FR system depending on outdoor access and this might have contributed to albumen quality and Haugh unit value of eggs.…”
Section: Discussioncontrasting
confidence: 53%
“…In this study generally the temperature was low in the FR system depending on outdoor access and this might have contributed to albumen quality and Haugh unit value of eggs. According to previous studies, the egg shape index (17) and yolk index (14) were higher in cage-system eggs than in the free-range or litter system eggs. However, Englmaierová et al (18) observed that the albumen and yolk index were higher in enriched cages and aviaries.…”
Section: Discussionmentioning
confidence: 78%
“…External egg quality, namely egg weight, poorer and variable eggshell quality, and shape index, and internal egg quality, namely proportion of yolk, albumen and lipid, depend on the age of laying hens (Rizzi & Chiericato, 2005;Johnston & Gous, 2007;Tůmová & Ledvinka, 2009;Charvátová & Tůmová, 2010). Egg weight, eggshell content, albumen height and albumen pH are affected by interactions between the age of laying hens, oviposition time and housing system ( Van den Brand et al, 2004;Tůmová et al, 2011).…”
Section: Introductionmentioning
confidence: 99%